1975
DOI: 10.1002/jhet.5570120504
|View full text |Cite
|
Sign up to set email alerts
|

2,3‐Dimethylquinoxaline‐6‐carboxaldehyde 1,4‐dioxide

Abstract: A series of derivatives of 2,3‐dimethylquinoxaline‐6‐carboxaldehyde 1,4‐dioxide was prepared. Derivatives prepared included nitrones, semicarbazide, and aminooxazolidinone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Culture supernatants from murine L. amazonensis-infected peritoneal macrophages treated with 17 M and 10.4 M concentrations of the compounds 8a and 14a, respectively, were collected after 48 h of incubation, and the nitrite content was determined by the Griess reaction procedure (26)(27)(28). Our results showed that both compounds (8a and 14a) were able to increase nitrite in the medium at 0.75 mM and 1.0 mM (Fig.…”
Section: Nitric Oxide Production (I)mentioning
confidence: 63%
See 2 more Smart Citations
“…Culture supernatants from murine L. amazonensis-infected peritoneal macrophages treated with 17 M and 10.4 M concentrations of the compounds 8a and 14a, respectively, were collected after 48 h of incubation, and the nitrite content was determined by the Griess reaction procedure (26)(27)(28). Our results showed that both compounds (8a and 14a) were able to increase nitrite in the medium at 0.75 mM and 1.0 mM (Fig.…”
Section: Nitric Oxide Production (I)mentioning
confidence: 63%
“…Compounds 2, 7, and 12 were synthesized according to a previously described methodology (24)(25)(26)(27). The compounds 2-, 3-, or 4-aminobenzohydrazide and 2-, 3-, or 4-hydroxybenzohydrazide were purchased commercially.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expansion process was performed, as previously reported, 5 with sodium methoxide as the base, the mixture of the benzofuroxan derivative [27][28][29][30] and the corresponding phenol in MeOH:THF as the solvent at low temperature. Under these conditions, the products were obtained in moderate yield, except for the highly reactive 5(6)-nitrobenzofuroxan, which produced a complex mixture of products and a low yield of the desired heterocycle (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The compounds 1, 2a, 2b, 5, 6, 10 and 13 were synthesized according to a previously described methodology [4][5][6][7][8][9]. of aminoguanidine hydrochloride (45mg; 0,4mmol) and 3mL of ethanol was stirred at room temperature for 2 to 3h and monitored by TLC (100% ethyl acetate).…”
Section: Chemistrymentioning
confidence: 99%